ChemInform Abstract: Dimethylzinc‐Mediated Chlorolactamization of Homoallylic Amines with Chloroform. Issue 21 (6th May 2016) - Nishida, Yuika; Ueda, Masafumi; Hayashi, Masataka; Takeda, Norihiko; Miyata, Okiko
Abstract: Treatment of homoallylic amines with dimethylzinc as radical initiator and chloroform as carbon source leads to the formation of the corresponding β‐chlorolactams via Prins‐type cyclization of a carbamoyl chloride intermediate.